Analysis of fungal deterioration phenomena in the first Portuguese King tomb using a multi-analytical approach. (April 2020) - Trovão, João; Gil, Francisco; Catarino, Lídia; Soares, Fabiana; Tiago, Igor; Portugal, António
Abstract: During the ongoing characterization of limestone biodeterioration in the UNESCO World Heritage site of "University of Coimbra – Alta and Sofia" (Coimbra, Portugal), it was brought to our attention that the limestone relieves adorning the tomb of D. Afonso I (First Portuguese King), displayed several signs of distinctive biodeterioration patterns. According to the ICOMOS Illustrated glossary on stone deterioration patterns, these could be characterized as visual mould proliferation, presence of black crusts, stone erosion and disintegration. Due to the invaluable nature of this monument, a multi-disciplinary approach (biological and analytical) to fully characterize these phenomena was applied. The results obtained allowed the characterization of the fungal diversity colonizing this monument, as well as the identification of various deterioration products. The results highlighted that the detected indoor black crusts displayed various characteristics from polluted environments, although lacking the typical association with gypsum. The black crusts were also characterized by the presence of lead oxides, damaging salts and carbonaceous particles. In addition, it could be verified that the erosion phenomena found are a result from fungal mediated calcium carbonate dissolution and calcium oxalate formation. The establishment of different fungal populations coupled with the deposition of environmental particles contributed to the development of the distinct phenomena detected through differential biodeterioration mechanisms. Highlights: Application of a multi analytical approach to study D. Afonso I tomb pathologies. High fungal contamination associated with all biodeteriorated areas. Black crusts holding lead oxides, anhydrite, syngenite and carbonaceous particles. Stone erosions with calcium oxalates. Biodeterioration by chromatic changes, stone dissolution and calcium oxalate formation.